Paragraph Selection Methods Using Feature-Based on Segment-Based Clustering Process Using Paragraphs for Identifying Topics on Indication Detection of Plagiarism System - Denar Regata Akbi; Arini Rahmawati Rosyadi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
In segment-based clustering, the paragraphs selection as a dataset in the clustering process has a very important role. This is because the paragraph used as the dataset can affect the clustering result. This research uses paragraph selection using feature-based method which aims to optimize the clustering process conducted in the previous research. Based on the evaluation results using Silhouette Coefficient and Sum Square Errors evaluation methods to find the proper k value, it is found that with the utilization of Feature-based method, better results can be acquire compared to the evaluation result from the previous research.